Analysis and modeling of education participation index (epi) in Indonesia from 2003-2008 - Usman, Mustofa; Hendarman, Henderman; Daoud, Jamal Ibrahim; Elfaki, Faiz Ahmed Mohamed (Penerbit UTHM, 2012)
The aims of the research is to reveal the characteristics of the Education Participation Index (EPI) in Indonesia based on the level of students’ age (7-12, 13-15, 16-18, and 19-24) which shows the participation index of the citizens at Elementary School, Junior High School, Senior High School and University. The data was taken from Central Bureau Statistics of Indonesia (BPS) from the year 2003 to 2008. The data is analyzed to see the difference between the level of ages at difference regions and difference years. And the data was analyzed by using analysis nested design. The second analysis is to find the EPI model for each regions and years. The modeling is used the multiple linear regression with dummy variable for the regions and years.